2013
DOI: 10.1002/art.37734
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose naltrexone for the treatment of fibromyalgia: Findings of a small, randomized, double‐blind, placebo‐controlled, counterbalanced, crossover trial assessing daily pain levels

Abstract: Objective. To determine whether low dosages (4.5 mg/day) of naltrexone reduce fibromyalgia severity as compared with the nonspecific effects of placebo. In this replication and extension study of a previous clinical trial, we tested the impact of low-dose naltrexone on daily self-reported pain. Secondary outcomes included general satisfaction with life, positive mood, sleep quality, and fatigue.Methods. Thirty-one women with fibromyalgia participated in the randomized, double-blind, placebocontrolled, counterb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 54 publications
4
136
1
5
Order By: Relevance
“…Degos et al [2013] mentioned that macrophages play a pivotal role in the development of neuroinflammation; they noticed that when blood-brain barrier permeability allows their migration into the hippocampus concomitant with proinflammatory cytokines, the inflammatory cascade is promoted. Younger et al [2013] reported that low-dose naltrexone has a beneficial effect on FMS pain, and they attributed this effect to the transient opioid blockade which causes a compensatory increase in endogenous opioid activity.…”
Section: Discussionmentioning
confidence: 99%
“…Degos et al [2013] mentioned that macrophages play a pivotal role in the development of neuroinflammation; they noticed that when blood-brain barrier permeability allows their migration into the hippocampus concomitant with proinflammatory cytokines, the inflammatory cascade is promoted. Younger et al [2013] reported that low-dose naltrexone has a beneficial effect on FMS pain, and they attributed this effect to the transient opioid blockade which causes a compensatory increase in endogenous opioid activity.…”
Section: Discussionmentioning
confidence: 99%
“…We illustrate how control engineering can accomplish this vision for behavioral interventions with the treatment of fibromyalgia (FM), a complex, multisymptom illness [10][11][12]. The approach is based on a secondary analysis of intensive longitudinal data collected in a previously conducted clinical trial that relied on low-dose naltrexone for the treatment of FM.…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence to suggest that naltrexone, an opioid antagonist, has a neuroprotective role and may be a potentially effective treatment for diseases like FM [11,35]. The data for this paper has been taken from clinical trials of a low-dose naltrexone (LDN) intervention [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Een recent getest medicament is de opioïd-antagonist naltrexon die in een lage dosis van 4,5 mg per dag bij fi bromyalgiepatiënten statistisch signifi cant meer pijnreductie bewerkstelligde dan een placebo, respectievelijk 28,8% en 18%. Het medicament had geen eff ect op vermoeidheid en slaapproblemen (Younger et al, 2013).…”
Section: Behandelingunclassified